Combining Ability for Yield and Associated Characters in Rice - Shrivastava, M.N.; Seshu, D.V. (Wiley, 1983)
Combining ability for yield and several related traits in rice (Oryza sativa L.), with a major focus on panicle characteristics, were studied in a 15 ✕ 15 diallel cross (excluding reciprocals). Eleven of the 15 parent cultivars were semidwarfs with broad resistance to various biological and physical stresses and four were traditional talls which still are popular with farmers. Variances for general combining ability (GCA) were significant for all the 16 traits studies; whereas, specific combining ability (SCA) variances were significant only for 12 of these. Specific combining ability was not important for number of spikelets per panicle and per secondary branch, effective length of primary branch, and width of grains. These traits can be utilized in developing highyielding homozygous lines. However, based on ratios obtained by comparing estimates of GCA and SCA variance components, SCA was more important than GCA for three of the characters including grain yield per plant. Heterogeneity of potence analysis confirmed that parental values do not completely predict F1 performance. Parents and cross combinations with high general and specific combining ability for various characters were identified. For grain yield per plant, the cultivars ‘CR1002’, ‘Leb Mue Nahng 111’, ‘IR42’, and ‘RPW617’ were found to be good general combiners, whereas the crosses ‘IR54’/‘PTB33’, ‘IR1060‐90’/‘RPW6‐17’ and ‘IR54’/‘LMN 111’ proved to be good specific combinations. The semidwarfing gene did not seem to limit the expression of some of the panicle traits that are important for further improvements over present yield levels of semidwarfs.